Relationships between emotional autonomy and parental nurturance with aggressive behaviour among pre-adolescents in Kuala Lumpur, Malaysia - Mehdinezhadnouri, Katayoun (2016)
Aggressive behaviour in pre-adolescents is a serious worldwide issue and it has developed into an internationally critical problems. Aggressive behaviour among preadolescents is considered to be unfavorable behaviour directed at other people possibly with the aim of harming them. Important factors related to aggressive behaviour during pre-adolescence are parental nurturance, and emotional autonomy. Pre-adolescents can increase their emotional autonomy by their close relationships with parents and enhance the ability to control and manage their behaviour in community. Therefore, this study was designed to examine the relationships between parental nurturance and emotional autonomy with aggressive behaviour by moderating role of age and gender among preadolescents.The multistage cluster sampling method was utilized to recruit a total of 390 preadolescents aged 10 to 12 years old from six primary schools in the urban areas of Kuala Lumpur, Malaysia. This study utilized quantitative study by using correlational research.Respondents completed the Parental Nurturance Scale (Lempers et al., 1989), Emotional Autonomy Scale (Steinberg and Silverberg, 1986), and Child Aggression Inventory (Maria Chong Abdullah et al., 2011). Correlational analyses indicated that preadolescents who perceived low parental nurturance and had low emotional autonomy were more likely to show aggressive behaviour. More so, pre-adolescent’s age and gender had relationships with aggressive behaviour. Additionally, the present research supported the moderating role of age on the relationships between parental nurturance and emotional autonomy with aggressive behaviour among pre-adolescents. Gender did not moderate these relationships. The findings of this research showed that parental nurturance and emotional autonomy were valuable predictors of aggressive behaviour among pre-adolescents. The current research improves understanding on the importance of parental nurturance and emotional autonomy as influencing factors on aggressive behaviour. The findings of this study can be useful for parents, teachers, counsellors, and policy makers to minimizing aggressive behaviour among pre-adolescents.